Molecular pathology of bone tumours: diagnostic implications. Issue 4 (31st October 2013) - Puls, Florian; Niblett, Angela J; Mangham, D Chas
<x xml:space="preserve">Abstract</x> Alongside histomorphology and immunohistochemistry, molecular pathology is now established as one of the cornerstones in the tissue diagnosis of bone tumours. We describe the principal molecular pathological techniques employed, and each of the bone tumour entities where their identified characteristic molecular pathological changes can be detected to support and confirm the suspected histological diagnosis. Tumours discussed include fibrous dysplasia, classical and subtype osteosarcomas, central and surface cartilaginous tumours, Ewing's sarcoma, vascular tumours, aneurysmal bone cyst, chordoma, myoepithelioma, and angiomatoid fibrous histiocytoma. This is a rapidly evolving field with discoveries occurring every few months, and some of the newer entities (the Ewing's‐like sarcomas), which are principally identified by their molecular pathology characteristics, are discussed.